2022
DOI: 10.1039/d1gc03798f
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of solubility parameters of lignin and ionic liquids using multi-resolution simulation approaches

Abstract: The solubility parameter (SP) of a molecular species is a vital feature that evaluates polarity and quantifies the ‘like-seeks-like' principle, which is used in chemistry to screen solvents for dissolution....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 73 publications
(123 reference statements)
2
33
0
Order By: Relevance
“…In addition, the results were further analyzed with Hansen solubility parameters (HSPs), and the performance of the HSP model has previously been demonstrated for lignin solubility using different solvent systems. 75 The HSP of a solvent or solute is broken down into three meaningful contributors, such as polar (δ p ), hydrogen-bonded (δ h ), and dispersion (δ d ) forces. It is a usual practice to depict a solvent as a point in Hansen's space, which is a three-dimensional space whose axis is comprised of the individual HSP contributors.…”
Section: Dissolution Of Lignin In Cyrene and Cyrene:watermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results were further analyzed with Hansen solubility parameters (HSPs), and the performance of the HSP model has previously been demonstrated for lignin solubility using different solvent systems. 75 The HSP of a solvent or solute is broken down into three meaningful contributors, such as polar (δ p ), hydrogen-bonded (δ h ), and dispersion (δ d ) forces. It is a usual practice to depict a solvent as a point in Hansen's space, which is a three-dimensional space whose axis is comprised of the individual HSP contributors.…”
Section: Dissolution Of Lignin In Cyrene and Cyrene:watermentioning
confidence: 99%
“…For good solvents, the value of RED should be less than 1 (i.e., R a < R 0 ). 75 The solubility of lignin in Cyrene, water, and Cyrene:water mixtures is analyzed and shown in Figure S3 (Supporting Information). Lower RED values indicate greater lignin solubility, and a 4:1 molar ratio of Cyrene to water results in lower RED values and greater lignin solubility.…”
Section: Dissolution Of Lignin In Cyrene and Cyrene:watermentioning
confidence: 99%
“…Based on the solubility parameters of benzothiophene and DFT calculations, it was also confirmed that both van der Waals (vdW) and electrostatic interactions played a predominant role in the extraction of the sulfur compound, whereas in the case of n-decane, the weak noncovalent interactions govern the extraction process based on solubility in the DES. 41,42…”
Section: Lle Results and Cosmo-sac Predictionmentioning
confidence: 99%
“…Yao et al extended the application of COSMO-RS prediction to demonstrate the synergistic advantages of multiple ions in a cholinium-based ionic liquid system for the pretreatment of sorghum biomass (Yao et al, 2021). Mood et al showed that solubility parameters of ionic liquids and deep eutectic solvents calculated using COSMO-RS are predictive of lignin solubility under the likedissolves-like principal and developed a new method to calculate solubility parameters from MD simulation trajectories, allowing predictions to be made for much larger lignin polymers (Mohan et al, 2021;Mohan et al, 2022).…”
Section: Understanding the Interactions Of Biomass With Pretreatment ...mentioning
confidence: 99%